2013
DOI: 10.2135/cropsci2013.05.0298
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Quantitative Trait Loci for Powdery Mildew Resistance in Flax (Linum usitatissimum L.)

Abstract: Powdery mildew (Oidium lini Skoric, [PM]), an obligate biotrophic ascomycete, is a common and widespread foliar disease of flax in most flax‐growing areas of the world. In this study, we constructed a linkage map using 143 simple sequence repeat (SSR) markers and an F2 population of 300 individuals generated from a cross between the susceptible cultivar NorMan and the resistant cultivar Linda. The F2–derived F3 families were phenotyped in the field and the F3–derived F4 families were phenotyped in a controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 78 publications
6
25
0
1
Order By: Relevance
“…In addition, the same QTL were also detected in the EV population as well as the merged population. Our association study also validated three QTL for YLD, DTM and PAL which were previously identified using linkage mapping using SSRs and SNPs [8,9] and from the association mapping using a flax core collection population with SSR markers [42] (Table 3). These verified QTL for fatty acid composition, seed yield and maturity demonstrate the feasibility of the association mapping method to detect QTL in a bi-parental population as well as a multi-parent population.…”
Section: Qtl Associated With Seed Yield and Seed Oil Quality Traitssupporting
confidence: 69%
“…In addition, the same QTL were also detected in the EV population as well as the merged population. Our association study also validated three QTL for YLD, DTM and PAL which were previously identified using linkage mapping using SSRs and SNPs [8,9] and from the association mapping using a flax core collection population with SSR markers [42] (Table 3). These verified QTL for fatty acid composition, seed yield and maturity demonstrate the feasibility of the association mapping method to detect QTL in a bi-parental population as well as a multi-parent population.…”
Section: Qtl Associated With Seed Yield and Seed Oil Quality Traitssupporting
confidence: 69%
“…All 313 flax QTL reported in the 14 studies (Table 2) were identified from three types of markers: amplified fragment length polymorphisms (AFLPs), SSRs, and SNPs. PCR primer sequences of AFLPs and SSRs were retrieved from the literature [15,[19][20][21]23,24]. For the SNPs named based on the scaffold sequences, their scaffold names and coordinates were collected directly from the publications [17,26].…”
Section: Marker Infomation Of Qtl In Flaxmentioning
confidence: 99%
“…These candidate genes can be further analysed and validated. For example, three QTL for powdery mildew resistance were identified [15] and mapped to chromosomes 1, 7, and 9 (Table 3, Figure 1). Some RGAs were found in the vicinity of the QTL, i.e., within the pre-defined window ( Table 4).…”
Section: Candidate Genes For Qtlmentioning
confidence: 99%
“…Phenotypic selection remains a major conventional breeding approach to improve traits of agronomic importance in flax. To accelerate the application of molecular breeding, a large number of molecular markers [11][12][13][14] and genetic populations [15][16][17][18] have been developed to assist QTL identification in the last decade. Using these genetic resources, a total of 267 QTL for 29 traits (11 seed yield and agronomic traits, 11 seed quality traits, four fibre traits, and three disease resistance traits) were reported in 13 studies (Tables 1 and 2).…”
mentioning
confidence: 99%
“…These QTL were identified mainly using SSR or SNP markers ( Table 2). Most (200) of the QTL were mapped based on genetic maps [15,[18][19][20][21][22][23][24], scaffold sequences [17,25,26], or an early (hereafter pre-released) version of chromosome-scale pseudomolecules (PCPs) [27,28]; however, only 67 QTL for pasmo severity (PAS) were mapped on the most recent release of the chromosome-scale pseudomolecules (RCPs) ( Table 2) [14,29]. For comparison purposes, coordinates of the QTL based on the PCPs must be converted to the RCPs [29] because the two versions are slightly different.…”
mentioning
confidence: 99%